Streptomyces: The biofactory of secondary metabolites - Alam, Khorshed; Mazumder, Arpita; Sikdar, Suranjana; Zhao, Yi-Ming; Hao, Jinfang; Song, Chaoyi; Wang, Yanyan; Sarkar, Rajib; Islam, Saiful; Zhang, Youming; Li, Aiying (Frontiers in Microbiology, 2022)
Natural products derived from microorganisms serve as a vital resource of valuable pharmaceuticals and therapeutic agents. Streptomyces is the most ubiquitous bacterial genus in the environments with prolific capability to produce diverse and valuable natural products with significant biological activities in medicine, environments, food industries, and agronomy sectors. However, many natural products remain unexplored among Streptomyces. It is exigent to develop novel antibiotics, agrochemicals, anticancer medicines, etc., due to the fast growth in resistance to antibiotics, cancer chemotherapeutics, and pesticides. This review article focused the natural products secreted by Streptomyces and their function and importance in curing diseases and agriculture. Moreover, it discussed genomic-driven drug discovery strategies and also gave a future perspective for drug development from the Streptomyces.